Role of regional anaesthesia for modified radical mastectomy in a hospital in Central India: a retrospective observational study - Gupta, Sumit Kumar; Garg, Arpit; Anne, Sirisha; Bhardwaj, Ajit (International Surgery Journal, 2021)
Background: The number of breast cancer surgeries in India are increasing in the recent years. Lifestyle changes and increased awareness are the two important factors contributing to the same. Newer methods of anaesthetic management are also being practised for overall benefit of the patient. Recent advances in the regional anaesthesia techniques especially under the guidance of ultrasonography, dramatically changed not only the operative outcomes but also the post-operative stay in the hospital. The present study was aimed to bring out differences between two popular options of opioid sparing regional anaesthesia techniques for post-operative analgesia for patients who had undergone modified radical mastectomy (MRM) for carcinoma breast at our centre. Methods: A total of 88 patients of ASA II and III grading were enrolled in the study who had received either of erector spinae plane block (ESB) or thoracic paravertebral block (TPVB). Post-op numerical rating scale for pain and analgesic requirements were compared between the two groups. Hemodynamic parameters were recorded for comparing the influence of the blocks on hemodynamics. Results: The demographic profile was similar between the 2 groups. The study showed that TPVB have a higher efficacy of analgesia when compared with that of ESB. However, there is no significant differences in the intra-op and post-op hemodynamics. Conclusions: In view of a higher safety profile of ESB, administration of the same may still be preferred over the TPVB especially in those with less experienced hands in patients undergoing modified radical mastectomy.